(untitled) (Journal of Asian Development Studies, 2018)
This paper attempts to examine the impact of foreign direct investment, remittances, foreign aid and trade openness (FCI’s) on tax revenue in Pakistan for the period 1975-2012. After data collection different econometric techniques like unit root test of ADF, Co integration and Error correction mechanism have been applied. The result shows that positive relationship exist between Remittances, Trade and tax revenue and negative relationship hold between FDI and total tax revenue in Pakistan during the study period.